HUBUNGAN POLA KONSUMSI PANGAN DAN STATUS SOSIAL EKONOMI KELUARGA DENGAN PERTUMBUHAN ANAK BARU MASUK SEKOLAH DI SD NEGERI NO.142442 KOTA PADANGSIDIMPUAN 2014 - ade Irma Harahap; Evawany Y Aritonang; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
The phase of school age is the most important in the next physical formation of kid. Physical qualities reflected from physical growth. Physical growth change will certainly seemed at the time of kid entered the age of school. The purpose of the research is to know the corelation between the food consumption patterns and social  economic of the family  with the growth of new kid entered the age of school  in elementary school padangsidimpuan no.142442. The type of research is descriptive using a cross sectional design. The population is all students in the first class of elementary school padang sidimpuan no.142442 . The sample as many as 54 of students taken with the technique of proportional sample.  Data about the consumption of food obtained through interviews directly to students who assisted by their mothers.  Data of the height of kid  measured with microtoise.  The growth of new kid entered school based  with  z-score height by age. Furthermore, to prove the hypothesis the chi-square test is used. The research showed 51,9 percent had height with short category,  40,7 percent normal and 7,4 percent kids were tall category. The analysis bivariat with chi-square test showing that there are significan  relationship between the level of family income(p = 0,037), kinds of food (p = 0,038),  the level of energy suffiency (p = 0,027) and the level of zinc suffiency (p = 0,044) with the growth of the new kid enter the school. There was not correlation with the variable of the level of mother’s educational, the level of mother’s occupation, the level of vitamin A sufficiency, the level of iodium sufficiency, the level of calcium sufficiency and the level of iron sufficiency with the growth of the new kid entered the school. It is hoped  the mothers provide multiform food being  for kids. Additionally, mothers should be pay attention to the level of nutrient sufficiency that will be consumed for a kid. Key words:  Food consumption pattern,  social economic of the family, the growth of new kid in school